2018
DOI: 10.3390/en11071728
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Optimization for Designing a Charging Station Based on Solar and Wind Energy for Electric Vehicles of a Smart Home in Small Villages

Abstract: In recent years, integration of electric vehicles (EVs) has increased dramatically due to their lower carbon emissions and reduced fossil fuel dependency. However, charging EVs could have significant impacts on the electrical grid. One promising method for mitigating these impacts is the use of renewable energy systems. Renewable energy systems can also be useful for charging EVs where there is no local grid. This paper proposes a new strategy for designing a renewable energy charging station consisting of win… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…& , the annual operation and maintenance (O&M) cost, can be specifically expressed in (44) - (47). 49) and (50).…”
Section: A Objective Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…& , the annual operation and maintenance (O&M) cost, can be specifically expressed in (44) - (47). 49) and (50).…”
Section: A Objective Functionmentioning
confidence: 99%
“…The electricity and service price of BSW are 0.122$/kWh and 0.1$/kWh. IV, referring to the latest reports and articles [47]- [50]. 10) The discount rate is assumed to be 0.06.…”
Section: A Case Description and Parameter Settingsmentioning
confidence: 99%
“…EV charging stations powered by solar or grid electric power are reviewed in [8]. Several studies have used wind energy for EV grid-connected mode [9,10] and off-grid stations [11]. Other studies [12,13] discussed design problems and proposed optimization methodologies for the size of EV charging stations in both solar and wind microgrids, and concluded that a mix of renewable energy sources and storage systems is best for the optimal design of EV charging stations.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies [12,13] discussed design problems and proposed optimization methodologies for the size of EV charging stations in both solar and wind microgrids, and concluded that a mix of renewable energy sources and storage systems is best for the optimal design of EV charging stations. Stand-alone solar and wind generators are not suitable sources to supply near-constant power for long periods, at least for slow power charging stations [8,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation